Resolvins activate inflammation-resolution programs: a systems approach to resolution - Serhan, Charles (Henry Stewart Talks, 2011)
New genus for pro-resolving lipid mediators, Resolvins & protectins, Metabolomics towards human treatment, Decision paths in acute Inflammation, Systems approach mapping resolution, Ideal inflammation outcome- complete resolution, Acute phase to resolution phase, Effects of Aspirin, Resolvins and Protectins- new mediator families, DHA metabolome, Pro-resolving lipid mediators, Resolution interval and failure of resolution in inflammatory diseases, RvE1 and RvD1- biosynthesis, structure and action, Pathogenesis of sepsis, RvD2, RvE1, RvD1 effects in inflammation, Self-limited evolving exudate, Resolvins are agonists that stimulate resolution
Reviewed at 2020/05/01